Adsorption of methyl tert-butyl ether (MTBE) onto ZSM-5 zeolite: Fixed-bed column tests, breakthrough curve modelling and regeneration. (April 2019) - Zhang, Yunhui; Jin, Fei; Shen, Zhengtao; Wang, Fei; Lynch, Rod; Al-Tabbaa, Abir
Abstract: ZSM-5, as a hydrophobic zeolite, has a good adsorption capacity for methyl tert -butyl ether (MTBE) in batch adsorption studies. This study explores the applicability of ZSM-5 as a reactive material in permeable reactive barriers (PRBs) to decontaminate the MTBE-containing groundwater. A series of laboratory scale fixed-bed column tests were carried out to determine the breakthrough curves and evaluate the adsorption performance of ZSM-5 towards MTBE under different operational conditions, including bed length, flow rate, initial MTBE concentration and ZSM-5 dosage, and regeneration tests were carried out at 80, 150 and 300 °C for 24 h. Dose-Response model was found to best describe the breakthrough curves. MTBE was effectively removed by the fixed-bed column packed with a ZSM-5/sand mixture with an adsorption capacity of 31.85 mg g −1 at 6 cm bed length, 1 mL min −1 flow rate, 300 mg L −1 initial MTBE concentration and 5% ZSM-5 dosage. The maximum adsorption capacity increased with the increase of bed length and the decrease of flow rate and MTBE concentration. The estimated kinetic parameters can be used to predict the dynamic behaviour of column systems. In addition, regeneration study shows that the adsorption capacity of ZSM-5 remains satisfactory (>85%) after up to four regeneration cycles. Highlights: ZSM-5 is evaluated on its removal for MTBE in fixed-bed column tests. Dose-Response model was found to best describe the breakthrough curves. The removal capacity is ∼31.85 mg g −1 in fixed-bed column tests. Parameters from BDST model can predict breakthrough curves at a new flow rate. ZSM-5 is effective and recyclable for MTBE contaminated groundwater remediation.